Acute hepatopancreatic necrosis disease in penaeid shrimp - Kumar, Ramya; Ng, Tze Hann; Wang, Han‐Ching (Reviews in aquaculture, 2020)
Asian countries are the major producers of cultured Penaeid shrimps such as Penaeus monodon and Penaeus (Litopenaeus) vannamei. In recent years, shrimp production has declined due to the emergence of a bacterial disease called acute hepatopancreatic necrosis disease (AHPND). This disease is mainly caused by Vibrio parahaemolyticus, but other Vibrio species are also known to cause AHPND in shrimps. Here, in addition to reviewing recent developments in the field of AHPND diagnosis, host responses to AHPND, the role of microbiota during AHPND infection and the current treatment options for AHPND, we also describe a model of AHPND pathogenesis.